(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The study aims to determine the effectiveness of virtual classes in developing competencies in food and beverages among BSHM students at Bestlink College of the Philippines. The study utilizes the descriptive method design for investigation and data collection. The researchers gathered data from 50 fourth-year college students through survey questionnaires administered via Google Forms during the academic year 2021-2022. The study aims to answer the following questions: (1) How many respondents of the 4th-year college students are described in terms of age, gender, and civil status? (2) What makes virtual classes effective regarding skills development of BSHM students relative to food and beverage? (3) What difficulties are the respondents encountering regarding the abovementioned variables? (4) How do BSHM college students perceive the effectiveness of virtual classroom approaches regarding skills development in food and beverages? (5) What recommendations may be crafted for the school administrators and faculty to improve virtual classes for BSHM students? The study will provide insights into the effectiveness of virtual classes in developing competencies in food and beverages among BSHM students.